The Mediating Role of Self-Compassion in the Relationship Between Academic Self-Efficacy and Academic Resilience Among University Students in Dhi Qar - Kamil Chyad Al-Rikabi, Ghaffar; Farhadi, Hadi; Najm Mohammed Aljawabir, Wisam; Yousefi, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to examine the mediating role of self-compassion in the relationship between academic self-efficacy and academic resilience among university students in Dhi Qar. Methods and Materials: This descriptive-correlational study employed a structural equation modeling approach. The statistical population included university students in Dhi Qar during the 2022–2023 academic year, and a total of 345 participants were selected using purposive sampling. Participants completed three standardized instruments: the Academic Resilience Scale (ARS), the Academic Self-Efficacy Questionnaire (ASEQ), and the Self-Compassion Scale (SCS). Descriptive statistics, Pearson correlation coefficients, multiple regression analysis, path analysis, and bootstrapping were used for data analysis via SPSS and AMOS version 23. Findings: The results showed that academic self-efficacy had a significant positive correlation with both self-compassion (r = 0.54, p < .01) and academic resilience (r = 0.53, p < .01), while self-compassion also correlated positively with academic resilience (r = 0.50, p < .01). Path analysis indicated that academic self-efficacy significantly predicted self-compassion (β = 0.519, p < .001) and academic resilience (β = 0.529, p < .001), explaining 26.9% and 27.9% of their variances, respectively. Self-compassion also had a significant direct effect on academic resilience (β = 0.461, p < .001), accounting for 21.2% of its variance. Bootstrap and Sobel test results confirmed the significant mediating role of self-compassion in the relationship between academic self-efficacy and academic resilience (indirect effect = 0.288, CI [0.201, 0.379]). Conclusion: The findings highlight the importance of self-compassion as a key emotional mechanism through which academic self-efficacy enhances academic resilience.